Pollution characteristics of black carbon based on MERRA-2 reanalysis data in core city of Central Plains Economic Zone, China: Historical trend and potential sources - Yan, Guangxuan; Yu, Hao; Li, Menghui; Zheng, Xueqing; Li, Shaohong; Yao, Dan; Liu, Menglin; Hu, Pengtuan (Frontiers in Environmental Science, 2022)
Black carbon (BC) is one of the main factors in global climate change and human health. Based on reanalysis data from the Modern-Era Retrospective Analysis for Research and Applications Version 2 (MERRA-2), the historical trends in the variation of BC and the factors affecting this were investigated in core city of Central Plains Economic Zone in China-Zhengzhou. Based on correlation analysis with ground measurements of BC concentration, it was determined that the MERRA-2 reanalysis data could be used to reveal the variations in ground-level BC concentrations. According to the variation trends of BC concentration in 1980–2020 and typical fossil fuel consumption in 2008–2017, two periods of rapidly increasing BC concentration were identified in 1980–1989 and 1999–2006. The increase in BC concentration then slowed from 2007. Since 2012, due to the adjustment of the Zhengzhou strategy and the implementation of an emission control strategy throughout Henan Province, the consumption of coal and coke decreased by 4% every year, resulting in a downward trend in the total BC emissions. However, coal and coke were still the main factors affecting the BC concentration in Zhengzhou. The contribution of transportation to BC in Zhengzhou has been particularly important since 2016. Analysis of BC seasonal variation revealed that the highest BC concentration was in winter, mainly due to the increase in industry and residential emissions. Additionally, based on the local and regional emission inventories and combined with potential source contribution function (PSCF), concentration weighted trajectory (CWT), this study revealed the potential sources regions and source types of BC in Zhengzhou, and found that the intensification of energy consumption and BC emissions in Zhengzhou and the surrounding regions of Henan Province might be the reasons for the high BC loading in Zhengzhou through regional transport.